Comparison of BARS and SKP Methods in Evaluating Lecturer Performance in Higher Education - Marta Ardiyanto; Ridwan Dwi Irawan; Kresna Agung Yudhianto (bit-Tech, 2025)
The evaluation of lecturer performance in higher education is vital for maintaining the quality of teaching, research, and community service. In Indonesia, civil servant lecturer assessments rely heavily on the Sasaran Kinerja Pegawai (SKP), which emphasizes quantitative indicators such as teaching load, publications, and community engagement. However, this approach often overlooks qualitative aspects, including teaching innovation, professional ethics, and student interaction. To address these gaps, this study proposes integrating the Behaviorally Anchored Rating Scale (BARS) with SKP to create a more comprehensive evaluation framework. The research, conducted at Universitas Duta Bangsa Surakarta in the 2024/2025 academic year, applied the Rapid Application Development (RAD) method to design a web-based prototype. Key stages included instrument design, weighting mechanisms, and reliability testing using Cronbach’s Alpha, which yielded a strong coefficient of 0.850. Evaluation involved six faculty leaders and eight rectorate leaders (bureau heads, vice rectors, and the rector), while the foundation board acted as validators to ensure objectivity. System testing demonstrated promising results: blackbox testing confirmed 100% functional accuracy, and usability testing showed an average satisfaction score of 4.2 out of 5 (84%). Findings indicate that combining SKP and BARS enhances accountability, transparency, and professional feedback. This model contributes practically to higher education human resource management by enabling data-driven decision-making and fostering lecturer development. While further validation across diverse institutions is needed, the integrated framework offers a more holistic and adaptive approach to lecturer performance evaluation.